Very Short Answer Type Questions (1MARK)
Very Short Answer Type Questions (1MARK)
Very Short Answer Type Questions (1MARK)
com/
om
Sol.
.c
∮ (𝑥) = 2𝑥 2 + 7𝑥 + 3
ns
io
∮ (−2) = 2(−2)2 + 7(−2) + 3
t
lu
= 8 − 14 + 3 = 11 − 14 = −3
so
𝟑
k
𝟐 𝟒𝒙𝟐
oo
Sol. Yes,
ce
3
.n
4𝑥 2 3 1
𝑥2 + = 𝑥 2 + 4𝑥 2 × 𝑥 −2
w
√𝑥
w
//w
3 1
= 𝑥 + 2
4𝑥 2−2 = 𝑥 2 + 4𝑥
s:
Sol.
(5 − 𝑦)2 = 25 + 𝑦 2 − 10𝑦. 𝐶𝑙𝑒𝑎𝑟𝑙𝑦 𝑡ℎ𝑒 𝑐𝑜𝑒𝑓𝑓𝑖𝑐𝑖𝑒𝑛𝑡 𝑜𝑓 𝑦 𝑖𝑠 − 10.
𝟏
Que 6. Find the value of polynomial 𝟏𝟐𝒙𝟐 − 𝟕𝒙 + 𝟏, 𝒘𝒉𝒆𝒏 𝒙 𝟒.
1 1 2 1 1 7
𝑝 ( ) = 12 × ( ) − 7 × + 1 = 12 × − +1
4 4 4 16 4
3 7 3−7+4 7−7
= − +1= = =0
4 4 4 4
om
Que 8. Find the value of 𝟓𝟏𝟑𝟐 − 𝟓𝟏𝟐𝟐 .
.c
5132 − 5122 = (513 + 512)(513 − 512)
ns
= 1025 × 1 = 1025
t io
lu
Que 9. Find the zero of the polynomial 𝒑(𝒙) = 𝟐𝒙 + 𝟑.
so
Sol. For zero of the Polynomial 𝑝(𝑥), 𝑤𝑒 𝑝𝑢𝑡 𝑝(𝑥) = 0 ⇒ 2𝑥 + 3 = 0
k
oo
3
⇒ 2𝑥 = −3 ⇒𝑥=−
rtb
2
ce
Sol. (i) Required polynomial should have one term with highest power of the variable 1.
tp
ht
Que 1. If x + 1 Is a factor of the polynomial 3x2 –kx, then find the value of k.
Sol. 𝐿𝑒𝑡 𝑝(𝑥) = 3𝑥 2 − 𝑘𝑥, 𝑎𝑠 (𝑥 + 1) 𝑖𝑠 𝑎 𝑓𝑎𝑐𝑡𝑜𝑟 𝑜𝑓 𝑝(𝑥)
𝑆𝑜, 𝑝(−1) = 0 𝑖. 𝑒., 3(−1)2 − 𝑘(−1) = 0 ⇒ 𝑘 = −3
Que 2. Find the value of k, if y+3 is a factor of 3y2 + ky + 6.
Sol. 𝐿𝑒𝑡 𝑝(𝑦) = 3𝑦 2 + 𝑘𝑦 + 6
om
𝐴𝑠 𝑦 + 3 𝑖𝑠 𝑎 𝑓𝑎𝑐𝑡𝑜𝑟 𝑜𝑓 𝑝(𝑦), 𝑠𝑜 𝑝(−3) = 0
.c
𝑖. 𝑒. , 3(−3)2 + 𝑘(−3) + 6 = 0
ns
io
⇒ 27 − 3𝑘 + 6 = 0 ⇒ 33 − 3𝑘 = 0
t
⇒ −3𝑘 = −33
lu
⇒ 𝑘 = 11
so
Que 3. Find the value of a, if x – a is a factor of x3 – ax2 + 2x + a – 1.
k
oo
⇒ 3𝑎 − 1 = 0
.n
w
1
w
⇒ 𝑎=
3
//w
2
⇒ ∮ (3√2) = (3√2) − 3√2(3√2) − 1 = 9 × 2 − 9 × 2 − 1 = −1
om
1
Sol. 𝑥 + 𝑥 = 4
.c
ns
1 2 1 1
io
⇒ (𝑥 ) = 42 ⇒ 𝑥 2 + 2 + 2𝑥 × = 16
𝑥 𝑥 𝑥
t
1
lu
so
⇒ 𝑥2 + = 16 − 2 = 14
𝑥2
k
oo
1
∴ 𝑥2 + = 14
rtb
𝑥2
ce
Que 10. Using factor theorem, show that (x- y) is a factor of 𝒙(𝒚𝟐 − 𝒛𝟐 ) +
𝒚(𝒛𝟐 − 𝒙𝟐 ) + 𝒛(𝒙𝟐 − 𝒚𝟐 ).
.n
w
= 𝑦(𝑦 2 − 𝑧 2 ) − 𝑦(𝑦 2 − 𝑧 2 ) = 0
ht
∮ (−2𝑘) = 0
(−2𝑘)5 − 4𝑘 2 (−2𝑘)3 + 2(−2𝑘) + 2𝑘 + 3 = 0
−32𝑘 5 + 32𝑘 5 − 4𝑘 + 2𝑘 + 3 = 0
3
⇒ −2𝑘 + 3 = 0 ⇒ −2𝑘 = −3 ⇒ 𝑘 =
2
om
Que 13. Find the remainder when ∮ (𝒙) = 𝟒𝒙𝟑 − 𝟏𝟐𝒙 + 𝟏𝟒𝒙 − 𝟑 is divided by
𝒈(𝒙) = (𝟐𝒙 − 𝟏).
.c
ns
Sol. 𝑇𝑎𝑘𝑖𝑛𝑔 𝑔(𝑥) = 0 𝑤𝑒 ℎ𝑎𝑣𝑒,
io
2𝑥 − 1 = 0
t
lu
so
1
⇒𝑥=
2
k
oo
1
By remainder theorem when ∮ (𝑥) is divided by 𝑔(𝑥), the remainder is equal to ∮ ( )
rtb
2
ce
1 1 3 1 2 1
w
∮ ( ) = 4 ( ) − 12 ( ) + 14 ( ) − 3
2 2 2 2
w
//w
1 1
= 4× − 12 × + 7 − 3
8 4
s:
tp
1 1 1
= −3+7−3= −6+7=1+
ht
2 2 2
1 3
∮( )=
2 2
3
Hence, required remainder = 2.
∴ ∮ (−1) = 0
om
⇒ 𝑘−3 = 0 ⇒𝑘 =3
.c
ns
Que 16. Expand using suitable identity (-2x+5y-3z) 2.
io
Sol. (−2𝑥 + 5𝑦 − 3𝑧)2
t
lu
= (−2𝑥)2 + (5𝑦)2 + (−3𝑧)2 + 2(−2𝑥)(5𝑦) + 2(5𝑦) (−3𝑧) + 2(−3𝑧)(−2𝑥)
k so
= 4𝑥 2 + 25𝑦 2 + 9𝑧 2 − 20𝑥𝑦 − 30𝑦𝑧 + 12𝑧𝑥
oo
rtb
𝟏 𝟏
Que 17. Find: 𝒙 + 𝒙 , 𝒊𝒇 𝒙𝟐 + 𝒙𝟐 = 𝟔𝟐.
ce
.n
Sol.
w
1 2 1 1
w
(𝑥 + ) = 𝑥 2 + 2 + 2. 𝑥.
//w
𝑥 𝑥 𝑥
1 2
s:
1 2
= 𝑥 + 2 + 2 = 62 + 2 = 64 ⇒ (𝑥 + ) = 64
tp
𝑥 𝑥
ht
1
Taking square root on both sides, we get 𝑥 + 𝑥 = 8.
𝟐𝟓 𝒚𝟐
Que 18. Factorise: 𝒙𝟐 − .
𝟒 𝟗
25𝑥 2 𝑦 2 5 2 𝑦 2 5 𝑦 5 𝑦
𝑆𝑜𝑙. − = ( 𝑥) − ( ) = ( 𝑥 + ) ( 𝑥 − )
4 9 2 3 2 3 2 3
Que 19. Find the value of k if (x – 2) is a factor of polynomial 𝒑(𝒙) = 𝟐𝒙𝟑 − 𝟔𝒙𝟐 +
𝟓𝒙 + 𝒌.
Sol. As (x – 2) is a factor of polynomial 𝑝(𝑥) = 2𝑥 3 − 6𝑥 2 + 5𝑥 + 𝑘, 𝑠𝑜, 𝑝(2) = 0
⇒ 2(2)3 − 6(2)2 + 5 × 2 + 𝑘 = 0
om
⇒ 16 − 24 + 10 + 𝑘 = 0
.c
ns
26 − 24 + 𝑘 = 0 ⇒ 𝑘 + 2 = 0 ⇒ 𝑘 = −2
io
Que 20. Factorise: 𝒂𝟐 + 𝒃𝟐 − 𝟐𝒃𝒄 + 𝟐𝒃𝒄 − 𝟐𝒄𝒂
t
Sol.
lu
𝑎2 + 𝑏 2 − 2𝑏𝑐 + 2𝑏𝑐 − 2𝑐𝑎 = (𝑎 − 𝑏)2 + 2𝑐(𝑏 − 𝑎) = (𝑎 − 𝑏)2 − 2𝑐(𝑎 − 𝑏)
so
k
= (𝑎 − 𝑏)(𝑎 − 𝑏 − 2𝑐) [𝑇𝑎𝑘𝑖𝑛𝑔 𝑐𝑜𝑚𝑚𝑜𝑛 (𝑎 − 𝑏)]
oo
𝑏)]
w
//w
Que 1. What must be subtracted from 𝒙𝟒 + 𝟑𝒙𝟑 + 𝟒𝒙𝟐 − 𝟑𝒙 – 𝟔 to get 𝟑𝒙𝟑 + 𝟒𝒙𝟐 −
𝒙+𝟑?
Sol. Let 𝑝(𝑥) be the required polynomial.
𝑇ℎ𝑒𝑛, 𝑥 4 + 3𝑥 3 + 4𝑥 2 − 3𝑥 − 6 − 𝑝(𝑥) = 3𝑥 3 + 4𝑥 2 − 𝑥 + 3
∴ 𝑝(𝑥) = 𝑥 4 + 3𝑥 3 + 4𝑥 2 − 3𝑥 − 6 − 3𝑥 3 − 4𝑥 2 + 𝑥 − 3
= 𝑥 4 − 2𝑥 − 9
om
Que 2. What must be added to 𝟐𝒙𝟐 − 𝟓𝒙 + 𝟔 𝒕𝒐 𝒈𝒆𝒕 𝒙𝟑 − 𝟑𝒙𝟐 + 𝟑𝒙 − 𝟓 ?
.c
Sol. Let 𝑝(𝑥) be added.
ns
𝑇ℎ𝑎𝑛, 2𝑥 2 − 5𝑥 + 6 + 𝑝(𝑥) = 𝑥 3 − 3𝑥 2 + 3𝑥 − 5
io
∴ 𝑝(𝑥) = 𝑥 3 − 3𝑥 2 + 3𝑥 − 5 − 2𝑥 2 + 5𝑥 – 6
t
lu
so
= 𝑥 3 − 5𝑥 2 + 8𝑥 – 11
k
𝑓(−2𝑘) = 0
w
w
16𝑘 4 − 16𝑘 4 − 4𝑘 + 3𝑘 + 3 = 0
s:
tp
⇒ −𝑘 + 3 = 0 ⇒ −𝑘 = −3 ⇒ 𝑘=3
ht
Now,
𝑓(𝑥) = 9𝑥 3 − 3𝑥 2 + 14𝑥 − 3
1 1 3 1 2 1
𝑓 (3) = 9 (3) − 3 (3) + 14 (3) − 3
1 1 14 1 1 14 1 5
= 9 × 27 − 3 × 9 + −3 = −3+ − 3 ⇒ 𝑓 (3) = 3
3 3 3
5
Hence, required remainder = =3
om
.c
Also,
ns
3 3 3 3 2 3
𝑝 (2) = 2 (2) − 9 (2) + + 12
io
2
t
lu
27 9 3
= 2× − 9 × 4 + 2 + 12
8
so
54 81 3 54−162+12+96 162−162 0
k
= − + 2 + 12 = = =8
oo
8 4 8 8
rtb
3
𝑝 (2) = 0
ce
Sol.
//w
−1
By factor theorem (2x – 1) will be a factor of p(x) if 𝑝 ( 2 ) = 0
ht
Now,
𝑝(𝑥) = 2𝑥 3 − 11𝑥 2 − 4𝑥 + 1
−1 −1 3 −1 2 −1
⇒ 𝑝 ( ) = 2 ( ) − 11 ( ) − 4 ( ) + 1
2 2 2 2
−1 1 1 1 11
= 2 ( ) − 11 × + 4 × + 1 = − − +2+1
8 4 2 4 4
−1 − 11 + 8 + 4 −12 + 12 −1
= = ⇒ 𝑝( ) = 0
4 4 2
−1
As 𝑝 ( 2 ) = 0, therefore (2x – 1) is a factor of 2𝑥 3 − 11𝑥 2 − 4𝑥 + 1.
Que 7. By actual division, find the quotient and remainder when 𝟑𝒙𝟒 − 𝟒𝒙𝟑 −
𝟑𝒙 – 𝟏 is divided by x + 1.
Sol. By long division, we have
om
.c
ns
io
t
lu
kso
oo
rtb
Sol. We have √𝑚 + √𝑛 − √𝑝 = 0
w
w
⇒ √𝑚 + √𝑛 = √𝑝
//w
s:
2 2
ht
⇒ 𝑚 + 𝑛 + 2√𝑚√𝑛 = 𝑝
⇒ 𝑚 + 𝑛 − 𝑝 = −2√𝑚𝑛
Again squaring both the sides, we get (𝑚 + 𝑛 − 𝑝)2 = 4𝑚𝑛
𝟏 𝒚 𝟑
Que 9. Expand: (𝒙 + 𝟑)
Sol.
1 𝑦 3 1 3 1 2𝑦 1 𝑦 2 𝑦 3
[ + ] = ( ) + 3( ) + 3 ( ) + ( )
𝑥 3 𝑥 𝑥 3 𝑥 3 3
1 3 12 𝑦 1 𝑦2 𝑦2
= ( ) + 3. ( 2 ) + 3. 2 + 3
𝑥 𝑥 3 𝑥3 3
1 𝑦 𝑦2 𝑦3
= + + +
𝑥 3 𝑥 2 3𝑥 27
Que 10. Evaluate: (104)3 using a suitable identity.
Sol. (104)3 = (100 + 4)3
Using identity (𝑥 + 𝑦)3 = 𝑥 3 + 3𝑥𝑦 (𝑥 + 𝑦) + 𝑦 3
We get,
(100 + 4)3 = (100)3 + 3 × 100 × 4(100 + 4) + 43
om
= 10,00,000 + 1,200 × 104 + 64
.c
= 10,00,000 + 1,24,800 + 64
ns
io
= 11,24,864
t
lu
Que 11. Evaluate 𝟏𝟎𝟓 × 𝟏𝟎𝟖 without multiplying directly.
so
Sol. 105 × 108 = (100 + 5) (100 + 8)
k
oo
Using identity (𝑥 + 𝑎) (𝑥 + 𝑏) = 𝑥 2 + (𝑎 + 𝑏) 𝑥 + 𝑎𝑏
rtb
𝟏 𝟏
Que 12. Find the value of 𝒙𝟐 + , 𝒊𝒇 𝒙 − 𝒙 = √𝟑.
w
𝒙𝟐
//w
1
Sol. 𝑥 − 𝑥 = √3
s:
tp
1 2 2
Squaring both the sides, we get (𝑥 − 𝑥) = (√3)
ht
1 1
⇒ 𝑥2 + − 2 × 𝑥 × = 3
𝑥2 𝑥
1 1
⇒ 𝑥2 + 2
= 3 + 2 ⇒ 𝑥2 + 2 = 5
𝑥 𝑥
Que 13. Factorise: 𝟓√𝟓𝒙𝟐 + 𝟑𝟎𝒙 + 𝟖√𝟓 by splitting the middle term.
om
= (5𝑥)3 + (3𝑦)3 + (2𝑧)3 − 3 × 5𝑥 × 3𝑦 × 2𝑧
.c
ns
= (5𝑥 + 3𝑦 + 2𝑧)[(5𝑥)2 + (3𝑦)2 + (2𝑧)2 − (5𝑥)(3𝑦) − (3𝑦)(2𝑧) − (2𝑧)(5𝑥)]
io
= (5𝑥 + 3𝑦 + 2𝑧)(25𝑥 2 + 9𝑦 2 + 4𝑧 2 − 15𝑥𝑦 − 6𝑦𝑧 − 10𝑧𝑥)
t
lu
so
𝐫𝟑 𝐬𝟑 𝐭𝟑 𝟏
Que 16. Factorise: − 𝟑𝟒𝟑 − 𝟐𝟏𝟔 − 𝒓𝒔𝒕.
𝟖 𝟐𝟖
k
oo
Sol.
rtb
𝑟3 𝑠3 𝑡3 1
− − − 𝑟𝑠𝑡.
ce
8 343 216 28
.n
𝑟 3 −𝑠 3 −𝑡 3 𝑟 −𝑠 −𝑡
w
( ) + ( ) + ( ) − 3( )( )( )
8 7 6 2 7 6
w
//w
𝑟 −𝑠 −𝑡 𝑟 2 −𝑠 −𝑡 2 𝑟 −𝑠 −𝑠 −𝑡 −𝑡 𝑟
= [ + ( ) + ( )] [( ) + ( ) + ( ) − ( ) − ( ) ( ) − ( ) ( )]
2 7 6 2 7 6 2 7 7 6 6 2
s:
tp
𝑟 𝑠 𝑡 𝑟 2 𝑠 2 𝑡 2 𝑟𝑠 𝑠𝑡 𝑡𝑟
ht
= ( − − )( + + + − + )
2 7 6 4 49 36 14 42 12
= 53 𝑥 3 − 73 𝑥 3 = (5𝑥)3 − (7𝑦)3
= (5𝑥 − 7𝑦)[(5𝑥)2 + 5𝑥. 7𝑦 + (7𝑦)2 ]
= (5𝑥 − 7𝑦)(25𝑥 2 + 35𝑥𝑦 + 49𝑦 2 )
om
2 2 1 2
.c
Que 20. Factorise: (5𝑟 + 3) − (2𝑟 − 3) .
ns
io
Sol.
t
lu
2 2 so1 2
(5𝑟 + ) − (2𝑟 − )
3 3
k
oo
2 1 2 1
= (5𝑟 + + 2𝑟 − ) [5𝑟 + − (2𝑟 − )]
3 3 3 3
rtb
2 1 2 1
ce
= (7𝑟 + − ) (5𝑟 − 2𝑟 + + )
3 3 3 3
.n
1
w
3
//w
s:
Que 21. Without actually calculating the cubes, find the value of:
tp
−3 3 −5 3 11 3
ht
( ) +( ) +( ) .
4 8 8
Sol. Let
−3 −5 11
𝑎= ,𝑏 = ,𝑐 =
4 8 8
−3 5 11
∴ 𝑎+𝑏+𝑐 = − +
4 8 8
−6 − 5 + 11
= =0
8
𝐼𝑓 𝑎 + 𝑏 = 0, 𝑡ℎ𝑒𝑛 𝑎3 + 𝑏 3 + 𝑐 3 = 3𝑎𝑏𝑐
−3 3 −5 3 11 3 −3 −5 11 495
∴ ( ) +( ) + ( ) = 3( )( )( ) =
4 8 8 4 8 8 256
Que 22. Without finding the cubes, factorise: (𝟐𝒓 − 𝟑𝒔)𝟑 + (𝟑𝒔 − 𝟓𝒕)𝟑 + (𝟓𝒕 − 𝟐𝒓)𝟑 .
Sol. Let 𝑎 = 2𝑟 − 3𝑠, 𝑏 = 3𝑠 − 5𝑡 + 5𝑡 − 2𝑟 = 0
∴ 𝑎 + 𝑏 + 𝑐 = 2𝑟 − 3𝑠 + 3𝑠 − 5𝑡 + 5𝑡 − 2𝑟 = 0
𝐼𝑓 𝑎 + 𝑏 + 𝑐 = 0, 𝑡ℎ𝑒𝑛 𝑎3 + 𝑏 3 + 𝑐 3 = 3𝑎𝑏𝑐
⇒ (2𝑟 − 3𝑠)3 + (3𝑠 − 5𝑡)3 + (5𝑡 − 2𝑟)3 = 3(2𝑟 − 3𝑠)(3𝑠 − 5𝑡)(5𝑡 − 2𝑟)
om
Sol.
.c
𝑥 3 − 8𝑦 3 − 216 − 36𝑥𝑦 = 𝑥 3 + (−2𝑦)3 + (−6)3 − 3. 𝑥(−2𝑦)(−6)
ns
= (𝑥 − 2𝑦 − 6)(𝑥 2 + 4𝑦 2 + 36 + 2𝑥𝑦 − 12𝑦 + 6𝑥)
tio
lu
∴ = 0 × (𝑥 2 + 4𝑦 2 + 36 + 2𝑥𝑦 − 12𝑦 + 6𝑥)[∵ 𝑥 = 2𝑦 + 6 ⇒ 𝑥 − 2𝑦 − 6 = 0]
so
=0
k
oo
𝒂𝟐 𝒃𝟐 𝒄𝟐
Que 24. If a, b, c are all non-zero and a + b + c = 0, prove that + 𝒄𝒂 + 𝒂𝒃 = 𝟑.
rtb
𝒃𝒄
Sol. We have,
ce
𝑎2 𝑏 2 𝑐 2
.n
+ + =3
w
𝑏𝑐 𝑐𝑎 𝑎𝑏
w
𝑎2 𝑏 2 𝑐 2 𝑎3 + 𝑏 3 + 𝑐 3
//w
𝐿𝐻𝑆 + + =
𝑏𝑐 𝑐𝑎 𝑎𝑏 𝑎𝑏𝑐
s:
3𝑎𝑏𝑐
tp
𝑎𝑏𝑐
om
𝟏 𝟐 𝟏 𝟐
Que 26. Factorise (𝟗𝒙 − 𝟓) − (𝒙 + 𝟑) .
.c
ns
1 2 1 2
Sol. We have, (9𝑥 − 5) − (𝑥 + 3) .
io
t
lu
1 1 1 1
= [(9𝑥 − ) − (𝑥 + )] [(9𝑥 − ) + (𝑥 )] [∵ 𝑎2 − 𝑏 2 = (𝑎 − 𝑏)(𝑎 + 𝑏)]
so
5 3 5 3
k
1 1 1 1
oo
= (9𝑥 − − 𝑥 − ) (9𝑥 − + 𝑥 + )
5 3 5 3
rtb
1 1 1 1
ce
= (8𝑥 − − ) (10𝑥 − + )
5 3 5 3
.n
120𝑥 − 3 − 5 150𝑥 − 3 + 5
w
=( )( )
15 15
w
//w
120𝑥 − 8 150𝑥 + 2
=( )( )
s:
15 15
tp
ht
om
∴ (𝑥 + 1) is a factor of 𝑝(𝑥)
.c
Putting 𝑥 𝑥 = 2 𝑖𝑛 𝑝(𝑥), we have
ns
𝑝(2) = 23 + 22 − 4 × 2 − 4
tio
lu
= −8 + 4 + 8 − 4
so
𝑝(−2) = 0
k
oo
∴ (𝑥 + 2) is a factor of 𝑝(𝑥).
rtb
As 𝑝(𝑥) is a polynomial of degree 3, so it cannot have more than three linear factors.
ce
= (𝑥 + 1)(𝑥 + 2)(𝑥 − 2)
s:
Que 2. Factorise: 𝒙𝟖 − 𝒚𝟖 .
tp
Sol. 𝑥 8 − 𝑦 8 = (𝑥 4 )2 − (𝑦 4 )2
ht
om
.c
ns
t io
lu
k so
oo
rtb
ce
.n
= (𝑥 + 2) [𝑥 2 + 10𝑥 + 𝑥 + 10]
w
om
= (𝑥 − 2)(2𝑥 2 + 6𝑥 − 5𝑥 − 15) = (𝑥 − 2)[2𝑥(𝑥 + 3) − 5(𝑥 + 3)]
.c
= (𝑥 − 2)[(𝑥 + 3)(2𝑥 − 5)] = (𝑥 − 2)(𝑥 + 3)(2𝑥 − 5)
ns
𝟏
io
Que 5. If both (𝒙 − 𝟐) and (𝒙 − 𝟐) are factors of 𝒑𝒙𝟐 + 𝟓𝒙 + 𝒓, Show that p = r.
t
Sol. 𝐿𝑒𝑡 𝑓(𝑥) = 𝑝𝑥 2 + 5𝑥 + 𝑟,
lu
so
k
As (𝑥 − 2 is a factor of 𝑓(𝑥), 𝑆𝑜 𝑓(2) = 0
oo
𝑝 × 22 + 5 × 2 + 𝑟 = 0
rtb
⇒ 4𝑝 + 10 + 𝑟 = 0 . . . . . . . . . . (𝑖)
ce
.n
1 1
Also (𝑥 − 2) is a factor of 𝑓(𝑥), 𝑠𝑜 𝑓(2) = 0
w
w
1 2 1
//w
𝑝 ( ) + 5. + 𝑟 = 0
2 2
s:
𝑝 5
tp
⇒ + +𝑟 =0 ⇒ 𝑝 + 10 + 4𝑟 = 0
4 2
ht
Then, 𝑞(𝑥) = 𝑥 2 + 3𝑥 + 2 = 𝑥 2 + 2𝑥 + 𝑥 + 2
= 𝑥(𝑥 + 2) + 1(𝑥 + 2) = (𝑥 + 2)(𝑥 + 1)
Now, 𝑝(−1) = 2(−1)4 + (−1)3 − 14(−1)2 − 19(−1) − 6
= 2 − 1 − 14 + 19 − 6 = 21 − 21
om
𝑝(−1) = 0
And, 𝑝(−2) = 2(−2)4 + (−2)3 − 14(−2)2 − 19(−2) − 6
.c
ns
= 32 − 8 − 56 + 38 − 6 = 70 − 70
t io
𝑝(−2) = 0
lu
so
⇒ (𝑥 + 1) 𝑎𝑛𝑑 (𝑥 + 2) are the factors of 𝑝(𝑥), 𝑠𝑜 𝑝(𝑥) is divisible by (𝑥 + 1) and (𝑥 + 2).
k
𝟏 𝒓
Que 7. Find the value of 𝟐𝟕 𝒓𝟑 − 𝒔𝟑 + 𝟏𝟐𝟓𝒕𝟑 + 𝟓𝒓𝒔𝒕, 𝒘𝒉𝒆𝒏 𝒔 = 𝟑 + 𝟓𝒕.
ce
1
.n
1 𝑟 3 𝑟
= 33 𝑟 3 + (−𝑠)3 + 53 𝑡 3 + 5𝑟𝑠𝑡 = (3) + (−𝑠)3 + (5𝑡)3 − 3 (3) (−𝑠)(5𝑡)
//w
𝑟 2
s:
𝑟 𝑟 𝑟
= ( 3 + (−𝑠) + 5𝑡) [(3) + (−𝑠)2 + (5𝑡)2 − 3 . (−𝑠) − (−𝑠)(5𝑡) − 3 (5𝑡)]
tp
ht
𝑟 𝑟2 𝑟𝑠 5𝑟𝑡
= ( 3 − 𝑠 + 5𝑡) ( + 𝑠 2 + 25𝑡 2 + + 5𝑠𝑡 − )
9 3 3
𝑟 𝑟
Now, 𝑠 = 3 + 5𝑡 (Given) ⇒ 3 − 𝑠 + 5𝑡 = 0
1 3 𝑟2 𝑟𝑠 5𝑟𝑡
∴ 𝑟 − 𝑠 3 + 125𝑡 3 + 5𝑟𝑠𝑡 = 0 × ( + 𝑠 2 + 25𝑡 2 + + 5𝑠𝑡 − )=0
27 9 3 3
𝟏 𝟏
Que 1. If z2 + = 14, find the value of z3 + 𝟑.
𝒛𝟐 𝒛
Sol. We have,
1 2 1 1
(𝑧 + 𝑧) = z2 + + 2z
𝑧2 𝑧
1 2 1 1 2
⇒ (𝑧 + 𝑧) = z2 + +2 ⇒ (𝑧 + 𝑧) = 14 + 2 = 16
𝑧2
1 2 1
⇒ (𝑧 + 𝑧) = 42 ⇒ z3 +
om
=4
𝑍
.c
1 3 1 1 1
⇒ (𝑧 + 𝑧) = 43 ⇒ z3 + + 3 x z x (𝑧 + ) = 64
ns
𝑧3 𝑧 𝑧
io
1 1
⇒ z3 + + 3 x 4 = 64 ⇒ z3 + = 64 – 12
t
𝑧3 𝑧3
lu
so
1
⇒ z3 + = 52
𝑧3
k
oo
𝟏 𝟏
Que 2. If 𝒙 + = 3, find the value of 𝒙4 + .
rtb
𝒙 𝒙𝟒
ce
1
Sol. We have 𝑥 + =3
𝑥
.n
w
1 2 1 2
//w
(𝑥 + 𝑥) = 32 ⇒ (𝑥 + 𝑥) = 9
s:
1 1 1
⇒ 𝑥2 + +2x𝑥x𝑥=9 ⇒ 𝑥2 +
tp
+2=9
𝑥2 𝑥2
ht
1 1
⇒ 𝑥2 + =9–2 ⇒ 𝑥2 + =7
𝑥2 𝑥2
1 1 2
Now, 𝑥2 + =7 ⇒ (𝑥 2 + ) = 72 ⇒ (𝑥2)2 +
𝑥2 𝑥2
1 1 1
⇒ 𝑥4 + + 2 = 49 ⇒ 𝑥4 + = 49 – 2 ⇒ 𝑥4 + = 47
𝑥4 𝑥4 𝑥4
P (3) = a x 33 + 4 x 32 + 3 x 3 – 4 = 27a + 36 + 9 – 4
P (3) = 27a + 41 …(i)
When q(z) is divided by z – 3 the remainder is given by,
q (3) = 33 – 4 x 3 + a = 27 – 12 + a
om
q (3) = 15 + a …(ii)
.c
According to question, p (3) = q (3)
ns
⇒ 27a + 41 = 15 + a ⇒ 27a – a = - 41 + 15
io
26a = - 26
t
lu
so
−26
⇒ a= ⇒ a=-1
26
k
oo
𝟏 𝟏
Que 4. If 𝒙2 + = 34, find 𝒙3 + – 9.
rtb
𝒙𝟐 𝒙𝟑
1 2
ce
1
Sol. (𝑥 + 𝑥) = 𝑥2 + + 2 = 34 + 2 = 36
𝑥2
.n
w
1
(𝑥 + 𝑥) = 6
w
//w
On cubing, we get
s:
1 3 1 1
(𝑥 + 𝑥) = 63 ⇒ 𝑥3 + + 3(𝑥 + 𝑥) = 216
tp
𝑥3
ht
1 1
⇒ 𝑥3 + + 3 x 6 = 216 ⇒ 𝑥3 + = 198
𝑥3 𝑥3
1
⇒ 𝑥3 + – 9 = 198 – 9 = 189
𝑥3
om
orphanage and 15 chocolates to adults working there. Taking the total items
.c
distributed as x and the number of children y, write a linear equation in two
ns
variables for the above situation.
(a) Write the equation in standard for.
io
ut
(b) How many children are there if total 61 items were distributed?
ol
(c) What values does Amisha possess?
ks
Sol. X = 2y + 15
oo
(a) x – 2y – 15 = 0
rtb
46
(b) 61 = 2y + 15 ⇒ y= = 23 children
2
ce
Que 2. The number of sincere students (x) in a class is two more than twice the
w
number of careless students (y). Write a linear equation in two variables for
//w
this situation. How does sincerity help and carelessness harm a student?
s:
Sol. X = 2 + 2y
tp
sincere students always progress in life as they value time and channelize their
ht
talent in productive activities while a careless student always wastes him talent and
time.